Pengaruh Social Media Marketing, Brand Image dan Kualitas Produk terhadap Keputusan Pembelian Sunscreen Azarine di Platform Tiktok - Desy Puspita Sari; Novita Wahyu Setyawati; Franciscus Dwikotjo Sri Sumantyo (Yayasan Inovasi Akademi Nusantara, 2025)
The research aims to determine the impact of Social Media Marketing, Brand Image and Product Quality on the Purchase Decision of Azarine Sunscreen on the TikTok Platform. This research is a quantitative approach study with a purposive sampling technique. Involving 112 respondents who are consumers of Azarine Sunscreen products in the Bhayangkara University Management Department Class of 2021. Data processing and hypothesis testing were carried out using SPSS 25 software. The results of the study reveal that there are variables that influence each other and those that do not influence each other, as explained below: 1) Social Media Marketing has no partial and significant effect on purchasing decisions; 2) Brand Image partially has a positive and significant effect on purchasing decisions; 3) Product Quality partially has a positive and significant effect on purchasing decisions; 4) Social Media Marketing, Brand Image and Product Quality simultaneously affect purchasing decisions.